Collaborative Governance Communication in Community-Based Traffic Safety Programs in Kendari City - Maudhy Satyadharma; Mahdar; Hado; Dwi Bayu Putra Pamungkas (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The issue of traffic safety in Kendari City has become a strategic and pressing concern due to the rapid increase in the number of vehicles, which is not adequately supported by proportional infrastructure development. This imbalance contributes significantly to rising traffic violations and accident rates. Conventional repressive approaches, such as law enforcement and punitive measures, are increasingly viewed as insufficient in fostering long-term behavioral change and collective public awareness. Therefore, there is a growing need for more collaborative, educational, and humanistic strategies that actively involve the community in promoting traffic safety. This study aims to analyze how local online media frames community-based traffic safety programs, with a particular focus on shaping public perception and awareness. The research employs a descriptive qualitative method within a constructivist paradigm, emphasizing how meaning is socially constructed through media narratives. The analysis is conducted using Entman’s framing model, which examines problem definition, causal interpretation, moral evaluation, and treatment recommendation within news coverage. The findings reveal that local media construct traffic safety issues through three dominant frames: individual responsibility, structural limitations, and integrative-participatory approaches. These frames highlight not only the role of individual behavior but also systemic challenges and the importance of collaborative engagement between stakeholders. Furthermore, the “Sahur on the Jack” program is consistently represented as an innovative and effective public communication strategy that fosters awareness, strengthens institutional synergy, and encourages active community participation. This study contributes to the broader discourse on collaborative governance and public communication by demonstrating how media framing can support adaptive and sustainable policy development in traffic safety management.